Neuroplasticity of Acupuncture for Stroke: An Evidence-Based Review of MRI - Jinhuan Zhang; Chunjian Lu; Xiaoxiong Wu; Dehui Nie; Haibo Yu (Neural Plasticity)
Acupuncture is widely recognized as a potentially effective treatment for stroke rehabilitation. Researchers in this area are actively investigating its therapeutic mechanisms. Magnetic resonance imaging (MRI), as a noninvasive, high anatomical resolution technique, has been employed to investigate neuroplasticity on acupuncture in stroke patients from a system level. However, there is no review on the mechanism of acupuncture treatment for stroke based on MRI. Therefore, we aim to summarize the current evidence about this aspect and provide useful information for future research. After searching PubMed, Web of Science, and Embase databases, 24 human and five animal studies were identified. This review focuses on the evidence on the possible mechanisms underlying mechanisms of acupuncture therapy in treating stroke by regulating brain plasticity. We found that acupuncture reorganizes not only motor-related network, including primary motor cortex (M1), premotor cortex, supplementary motor area (SMA), frontoparietal network (LFPN and RFPN), and sensorimotor network (SMN), as well as default mode network (aDMN and pDMN), but also language-related brain areas including inferior frontal gyrus frontal, temporal, parietal, and occipital lobes, as well as cognition-related brain regions. In addition, acupuncture therapy can modulate the function and structural plasticity of post-stroke, which may be linked to the mechanism effect of acupuncture.